Examining the Geospatial Distribution of Health and Support Services for Transgender, Gender Nonbinary, and Other Gender Diverse People in New York City - Liadh Timmins (Transgender Health, 2022)
A geospatial analysis of services that support transgender and gender diverse (“trans”) people in New York City (NYC) was conducted to investigate associations with neighborhood-level sociodemographic characteristics. In June 2019, there were 5.3 services for every 100,000 of the general NYC population; controlling for other covariates, they were more commonly located in neighborhoods with larger populations of non-Hispanic Black (rate ratio [RR]=1.02, 95% confidence interval [CI]: 1.00–1.04), Hispanic/Latino (RR=1.03, 95% CI: 1.00–1.06), and gay/lesbian people (RR=1.53, 95% CI: 1.03–2.34). These findings suggest that the distribution of trans-focused services in NYC is proximal to communities that are most in need, but research should examine proximity to trans people specifically and distribution in nonurban areas.